Austrocnephia, new genus, for five species of ‘Paracnephia’ (Diptera: Simuliidae), with a key to Australian black fly genera - Craig, Douglas A.; Currie, Douglas C.; Gil-Azevedo, Leonardo H.; Moulton, John K. (Zootaxa, 2019)
A segregate of the so-called Australian ‘Paracnephia’ (Diptera: Simuliidae) is assigned to a new genus, Austrocnephia. The taxon is fully diagnosed and a key to constituent species presented. Two species-groups are recognized: the aurantiaca species-group, comprised of A. aurantiaca (Tonnoir 1925) and A. strenua (Mackerras & Mackerras 1950), and the tonnoiri species-group, comprised of A. fuscoflava (Mackerras & Mackerras 1948), A. orientalis (Mackerras & Mackerras 1950) and A. tonnoiri (Drummond 1931). Both species-groups are diagnosed and the included species fully redescribed. Detailed locality data is given, as is information about biology, when known. Brief comments are offered about the historical biogeography of Austrocnephia. A key to Australian simuliid genera is also provided.